2018
DOI: 10.1016/j.scitotenv.2017.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Modelling regional cropping patterns under scenarios of climate and socio-economic change in Hungary

Abstract: Impacts of socio-economic, political and climatic change on agricultural land systems are inherently uncertain. The role of regional and local-level actors is critical in developing effective policy responses that accommodate such uncertainty in a flexible and informed way across governance levels. This study identified potential regional challenges in arable land use systems, which may arise from climate and socio-economic change for two counties in western Hungary: Veszprém and Tolna. An empirically-grounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…As a consequence, ABM simulations result in broadly similar development of land cover maps despite partly pronounced differences in the assumed future development of prices, subsidies, income and workload. It might, however, be that future climate change and/or societal changes will encourage or even force land owners to consider new farming strategies beyond what currently appears conceivable to them (Li, Juhász‐Horváth, Pintér, Rounsevell, & Harrison, ; Trnka et al, ). Coupling land‐use and climate scenarios such that they integrate possible climatic effects on yields, prices and workloads associated with currently grown or alternative crops and cultivars could be an appropriate way towards widening the perceived option space of agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, ABM simulations result in broadly similar development of land cover maps despite partly pronounced differences in the assumed future development of prices, subsidies, income and workload. It might, however, be that future climate change and/or societal changes will encourage or even force land owners to consider new farming strategies beyond what currently appears conceivable to them (Li, Juhász‐Horváth, Pintér, Rounsevell, & Harrison, ; Trnka et al, ). Coupling land‐use and climate scenarios such that they integrate possible climatic effects on yields, prices and workloads associated with currently grown or alternative crops and cultivars could be an appropriate way towards widening the perceived option space of agents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of land use in the SDMs, the impact of landuse scenarios on potential future plant distribution in the study region is much weaker than the impact of climatic scenarios. The apparent contradiction is explained by the modest changes in land use predicted farming strategies beyond what currently appears conceivable to them (Li, Juhász-Horváth, Pintér, Rounsevell, & Harrison, 2018;Trnka et al, 2009). Coupling land-use and climate scenarios such that they integrate possible climatic effects on yields, prices and workloads associated with currently grown or alternative crops and cultivars could be an appropriate way towards widening the perceived option space of agents.…”
Section: Land-use Change Effectsmentioning
confidence: 99%
“…For example, the driving factor of cropland abandonment in Eastern Europe is institutional change [45], while in Australia, Portugal and Sweden it is socioeconomic development [17]. In general, changes in human factors (e.g., technology, institutions, and the economy) have contributed to the layout of the cropland landscape in Europe [46][47][48]. However, the impact of the natural environment on cropland abandonment should not be ignored in in-depth research [48][49][50], as changes in land use may be affected by both the natural and social environments.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…When introducing these results in public participation processes, it would be helpful to bridge the landscape indices with their implication on sustainability, meanwhile hiding the computational complexity. Studies have shown that introducing urban morphological parameters in urban modelling could yield more accurate projections and could facilitate stakeholder discussion on developing future urban developmental scenarios [34,60]. However, the implications of these indices might remain vague for the general public, as the scale of the current study was coarse.…”
Section: Implications Of Changes In Landscape Indices For Sustainablementioning
confidence: 90%